ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN CURRENCY SWAP SEBAGAI ALAT LINDUNG NILAI (Studi Kasus Pada Bank yang Tedaftar di Bursa Efek Indonesia Pada Tahun 2009-2014) - Kartika, Felicia; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
The evelopment of the economy that becomes more global makes general banks to use foreign currencies in a transaction at a certain time or circumstances. Foreign currencies’ values are fluctuating that could lead a bank to exposure of the exchange rate risk. Currency swap contract is an alternative that can be used by the bank to do a hedge. This research aims to analyze how the foreign exchange liabilities, bank size, cost of financial distress, and net open position affecting the use of currency swap on general banks that listed in Indonesia Stock Exchange. After the literature review, data were collected by documentary study of financial reports and formed the pooled data. The pooled data then being analyzed using some methods like descriptive statistic analysis, the test of classical assumption, linear regression analysis, and the goodness of fit regression model. The result of this research shows that foreign exchange of liabilities, bank size, and net open position are significantly against the decision of using currency swap as a hedge significantly, while the cost of financial distress does not significantly against the decision of using currency swap as a hedge.